Clip culture. (Economist, 2006)
The article discusses the internet software company YouTube, owned by Chad Hurley and Steve Chen. The company was designed to allow people to share home videos online in a user-friendly fashion. The author reports that the company competes with Google Video, another video-clip viewing software company, but seems to be doing a lot better than Google.